MalaCards: A Comprehensive Automatically‐Mined Database of Human Diseases. Issue 1 (8th September 2014) - Rappaport, Noa; Twik, Michal; Nativ, Noam; Stelzer, Gil; Bahir, Iris; Stein, Tsippi Iny; Safran, Marilyn; Lancet, Doron
Abstract: Systems medicine provides insights into mechanisms of human diseases, and expedites the development of better diagnostics and drugs. To facilitate such strategies, we initiated MalaCards, a compendium of human diseases and their annotations, integrating and often remodeling information from 64 data sources. MalaCards employs, among others, the proven automatic data‐mining strategies established in the construction of GeneCards, our widely used compendium of human genes. The development of MalaCards poses many algorithmic challenges, such as disease name unification, integrated classification, gene‐disease association, and disease‐targeted expression analysis. MalaCards displays a Web card for each of >19, 000 human diseases, with 17 sections, including textual summaries, related diseases, related genes, genetic variations and tests, and relevant publications. Also included are a powerful search engine and a variety of categorized disease lists. This unit describes two basic protocols to search and browse MalaCards effectively. Curr. Protoc. Bioinform . 47:1.24.1‐1.24.19. © 2014 by John Wiley & Sons, Inc.